Implementasi Machine Learning Untuk Prediksi Kemungkinan Penyakit Stroke Berbasis Web - Alpi Sulaiha; Meiliyani Br Ginting; Ita Margarett Br Tarigan (JISTI: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2026)
Effective campus promotion activities are essential to enhance the visibility and appeal of the Institute of Technology and Business. This monitoring system aims to optimize campus promotional strategies through the use of the Rapid Application Development (RAD) method, which enables quick and adaptive system development according to needs. The system will help monitor and evaluate the effectiveness of promotional activities in real-time, providing accurate data for analysis and strategic decision-making by campus management.With this system, it is expected to increase the number of new student applicants and expand the campus's promotional reach to a broader target audience. Based on the above issues, the author designed a campus promotion activity monitoring system using the RAD method.